2018
DOI: 10.5604/01.3001.0012.0931
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Neutrophil Gelatinase-Associated Lipocalin in Cirrhotic Patients with Acute Kidney Injury

Abstract: A single baseline measurement of uNGAL level has the ability to determine type of kidney dysfunction in cirrhotic patients, perhaps accelerating management decisions and improving outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…The 30-day and 1-year mortality rates in our study were 28.5% and 50%, similar to those reported in western cohorts 2,[27][28][29] . Previous studies have shown uNGAL levels' association with adverse in-hospital outcomes including mortality, which was likewise demonstrated in our study 18,[30][31][32][33][34][35] . However, there is a paucity of data contributing to the evidence base regarding associations between uNGAL and long-term renal outcomes after AKI.…”
Section: Discussionsupporting
confidence: 90%
“…The 30-day and 1-year mortality rates in our study were 28.5% and 50%, similar to those reported in western cohorts 2,[27][28][29] . Previous studies have shown uNGAL levels' association with adverse in-hospital outcomes including mortality, which was likewise demonstrated in our study 18,[30][31][32][33][34][35] . However, there is a paucity of data contributing to the evidence base regarding associations between uNGAL and long-term renal outcomes after AKI.…”
Section: Discussionsupporting
confidence: 90%
“…Although considered standard tools in routine clinical tests, serum creatinine concentration and urine output are not suitable for the early detection of AKI, owing to inherent methodological problems. [2] Many potential biomarkers for the early detection of AKI have been identified, [3] including neutrophil gelatinase-associated lipocalin (NGA L), [4] N-acetyl-b-D-glucosaminidase (NAG), [5] interleukin 18 (IL-18), [6] glutathione S-transferase (GST), [7] kidney injury molecule-1 (KIM-1), [8] and liver-type fatty acid-binding protein (L-FABP). [9] More recently, urinary tissue inhibitor of metalloproteinase-2 (TIMP-2) and insulin-like growth factor binding protein 7 (IGFBP7) were reported to be superior to other biomarkers of AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the calculation of GFR is also limited in clinic due to oliguria or other disturbance factors. Recently, NGAL as a novel marker for renal injury has been suggested to be an excellent predictor of AKI in several pathological conditions like circulatory shock, cirrhosis, and sepsis . The novel role of NGAL in CNS diseases such as EAE, TBI, and cerebral aneurysms has been highlighted gradually .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, NGAL as a novel marker for renal injury has been suggested to be an excellent predictor of AKI in several pathological conditions like circulatory shock, cirrhosis, and sepsis. [21][22][23] The novel role of NGAL in CNS diseases such as EAE, TBI, and cerebral aneurysms has been highlighted gradually. 10,12,13 Here, we found the high level of serum NGAL occurred in the AIS patients with AKI and its level was correlated positively with the level of serum creatinine, suggesting that serum NGAL may reflect the change and severity of renal function in the early stage of AIS.…”
Section: Discussionmentioning
confidence: 99%